Injured submucosal arteries following cold snare polypectomy are significantly fewer versus those after endoscopic mucosal resection for 10–19‐mm nonpedunculated colorectal polyps - Shingo Kurasawa; Ichitaro Horiuchi; Masashi Kajiyama; Hiroe Kitahara; Tsuyoshi Terashima; Akira Horiuchi (DEN Open)
Abstract Objectives We compared the frequency of post‐polypectomy bleeding or injured submucosal arteries between cold snare polypectomy (CSP) and endoscopic mucosal resection (EMR) for nonpedunculated colorectal polyps. Methods This was a prospective, randomized, single‐center study. Patients who underwent CSP or EMR for 10–19‐mm nonpedunculated polyps were enrolled in CSP and EMR groups, and we compared the patient and polyp characteristics, the number of clips used, clinical outcomes, adverse events, and pathological features of the resected polyps between these groups. The primary outcome was the presence of injured arteries in the submucosal layer of the resected polyps examined histologically. The secondary outcomes were immediate bleeding and delayed bleeding. Results Fifty‐three patients with 60 eligible polyps were enrolled. The numbers of polyps/patients were 30/26 in the CSP group and 30/27 in the EMR group. The patient and polyp characteristics were similar between the groups. The total number of hemostatic clips used for hemostasis or prophylactic clipping was significantly greater in the EMR group compared to the CSP group (78 vs. 10, p < 0.001). The frequency of immediate bleeding after CSP was similar to that after EMR [6.7% (2/30) vs. 13% (4/30), p = 0.39]. Delayed bleeding did not occur in either group. The presence of injured submucosal arteries after CSP was significantly less frequent than that after EMR: 10% (3/30) versus 67% (20/30), p < 0.001. Conclusions In the resection of 10–19‐mm nonpedunculated colorectal polyps, CSP may decrease post‐polypectomy bleeding without prophylactic clipping compared to EMR as it results in fewer injured submucosal arteries. www.clinicaltrials.gov (NCT05930041).